2001
DOI: 10.4319/lo.2001.46.6.1400
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of Heterosigma akashiwo do not appear to be mediated by hydrogen peroxide

Abstract: The ichthyotoxic red tide organism Heterosigma akashiwo (Raphidophyceae) has been associated with fish kill events within the aquaculture industry for many years. The precise toxicological mechanism involved in these fish kills is unclear; however, much research attention has focused on the production of reactive oxygen species (ROS) by these toxic algae. In this study, we investigated the production of hydrogen peroxide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 24 publications
3
46
0
Order By: Relevance
“…Bioactive substance(s) were still active after heating and freezing (20% and 70% of original activity), characteristics that argue against a role for ROS that are chemically unstable. Twiner et al (2001) concluded that peroxide was not produced in sufficient amounts by the raphidophyte Heterosigma akashiwo to affect vertebrate cell lines but extracellular organic components did (Twiner et al, 2004(Twiner et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive substance(s) were still active after heating and freezing (20% and 70% of original activity), characteristics that argue against a role for ROS that are chemically unstable. Twiner et al (2001) concluded that peroxide was not produced in sufficient amounts by the raphidophyte Heterosigma akashiwo to affect vertebrate cell lines but extracellular organic components did (Twiner et al, 2004(Twiner et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The literature offers considerable discussion and debate on the subject (see references in 'Introduction', also Twiner et al 2001, Cembella 2003. Damage to fish gill tissue by ROS is clearly an element of the ichthyotoxicity caused by this and related raphidophytes (Yang et al 1995, Kim et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it had been shown allelopathic effects towards other algae, specifically diatoms [30]. The growth and toxicity of H. akashiwo can be mediated by hydrogen peroxide [24,31] or viruses [32,33]. In addition, and more relevant to the blooms H. akashiwo in a climate change environment, [34] showed that growth and toxicity of this alga was markedly influenced by changes in temperature and light intensity.…”
Section: Introductionmentioning
confidence: 99%